Hubungan kadar serum albumin dengan kejadian morbiditas dan mortalitas pada pasien penyakit ginjal kronik dengan hemodialisis di RS Dr. Sardjito Yogyakarta - La Banudi; Ahmad Husain Asdie; Susetyowati Susetyowati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Chronic kidney disease is a characterized by decreasing kidney function with creatine clearance test <15 mL/minute. At such condition toxic in the body accumulates so that dialysis is needed to eliminate it. Blood albumin serum level may indicate nutrition status and is closely related to morbidity and mortality of hemodialysis patients.Objective: To find out association between albumin serum level and occurrence of morbidity and mortality among patients of chronic kidney disease with hemodialysis.Method: The study was observational with prospective cohort design. It was conducted at Dialysis Installation of Dr. Sardjito Hospital from August 2004 to December 2005. Population were all patients of hemodialysis. Samples were purposively taken using inclusion criteria with as many as 44 minimal samples. Dependent variables were morbidity and mortality. Independent variables were albumin serum level, age and long time hemodialysis. Data analysis was done in phases, univariable, and then bivariable.Results: There was association between albumin serum level and morbidity at observation I (p=0.021), observation II (p=0.036), and observation III (p=0.012) which indicated that p<0.05. There was also association between albumin serum level and mortality at observation I (p=0.011), observation II, III and IV (p=0.000) which indicated that p<0.05.Conclusion: There was association between albumin serum level and morbidity and mortality of chronic kidney disease patients with hemodialysis.